We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
146
1
avatar+4116 

Help 

 Oct 15, 2018
 #1
avatar+102396 
+3

f(n)  =  ( n + 2)^2  + n^2  - 4  

 

f(n)  =  (n + 2) (n + 2) + n^2  - 4

 

f(n)  = n^2 + 4n + 4  + n^2  - 4

 

f(n)  = 2n^2 + 4n

 

f(n)  =   n(2n + 4)

 

 

cool cool cool

 Oct 15, 2018

15 Online Users

avatar